Clarifying the Conceptual Divide Between Descriptive Research and Qualitative Inquiry in Health Sciences - Heru Santoso Wahito Nugroho (Health Notions, 2026)
The persistent conflation between descriptive research and qualitative research remains a recurring methodological problem in health‑science publications, particularly in manuscripts submitted to Health Notions. This conceptual ambiguity undermines the rigor of study design and weakens the interpretive value of research findings. The objective of this editorial is to clarify the epistemological and methodological distinctions between descriptive research and qualitative inquiry, while illustrating their implications through examples drawn from public health and clinical practice. Using a conceptual‑analytic approach, this article examines the philosophical foundations, research logic, and practical applications of both approaches. The analysis shows that descriptive research, rooted in the quantitative paradigm, focuses on mapping the distribution of health variables; such as the prevalence of hypertension, maternal anemia, or tuberculosis treatment default without explaining the contextual or experiential dimensions underlying these patterns. In contrast, qualitative research seeks to interpret meaning, explore lived experiences, and uncover cultural, social, and behavioral factors that shape health phenomena, such as patients’ fears of medication, stigma surrounding tuberculosis, or cultural taboos influencing maternal nutrition. The findings emphasize that misunderstanding these distinctions leads to methodological misalignment, weak theoretical contribution, and incomplete evidence for policy and practice. The editorial concludes that descriptive and qualitative research are not interchangeable but complementary, and that methodological clarity is essential for producing robust, contextually grounded health evidence. Strengthening this conceptual distinction will enhance the quality of manuscripts submitted to Health Notions and support more effective health‑system decision‑making.Keywords: Keywords: descriptive research; qualitative research; methodology; health sciences; research approach